Oxymatrine relieves high-fructose/fat-induced obesity via reprogramming the activity of lipid metabolism-related enhancer - Ren, Luping; Liu, Xuehua; Huang, Xitong; Zhang, He; Fei, Wenjie; Yu, Xian; Hu, Zhijuan; Zhen, Yunfeng; Chen, Shuchun (Frontiers in Endocrinology, 2023)
Emerging evidence demonstrates that the high-fructose and high-fat diet (HFHF) induced obesity and fatty liver disease has become one of the most common metabolic disorders worldwide. Therefore, innovative investigations on compounds targeting obesity and fatty liver disease are urgently needed. Through the high-throughput natural compounds screen, we identified Oxymatrine, a natural compound extracted from Sophora flavescens, showed a potential compacity in high-fat diet-induced fatty liver disease. However, the regulatory function of Oxymatrine in metabolic disorder-related disease remains largely explored. Here, we systematically investigated the impact of oxymatrine on HFHF-induced obesity. We found that oxymatrine significantly inhibited HFHF-induced obesity using a rat HFHF model. Additionally, we found that oxymatrine altered the enhancer landscape of subcutaneous adipose tissues by ChIP-seq analysis using antibodies against the H3K27ac histone modification. Motif enrichment analysis showed the Smad motif was significantly enriched in enhancers altered post-oxymatrine treatment. Further ChIP-qPCR analysis and luciferase reporter assays showed oxymatrine alters the binding of Smad3 on the enhancer regions of Bcl2 and the enhancer activity of Bcl2. Together, our study highlighted oxymatrine could suppress high-fructose and high-fat diet-induced obesity by inhibiting Smad3 binding on obesity-related enhancers.